Master your Mac - Cone, Matthew (No Starch Press, 2012)
Mac OS X is so easy a monkey could use it, right? Well, half right. Beneath that glossy surface the fearless user will find lots of powerful features that aren't immediately obvious. Master Your Mac aims to help users cross that divide.